The subgenus Pentapedilum Kieffer (Diptera: Chironomidae) in the Yaeyama Islands, the Ryukyus, Japan - Yamamoto, Nao; Hirowatari, Toshiya; Yamamoto, Masaru (Zootaxa, 2012)
As a result of a multi-year survey, we recognize three Pentapedilum species, including a new species, from Iriomote Is-land, Japan. Polypedilum (Pentapedilum) acristylum sp. nov. is described as adult male, and compared with the closest P.(Pe.) nodosum Johannsen, 1932.Pentapedilum iriodeeum Sasa et Suzuki, 2000 is treated as a junior synonym of P. (Tripodura) tananense Sasa etHasegawa, 1988. Since the subgenus Pentapedilum Kieffer, 1913 defined solely by the presence of macrotrichia on thewing membrane may not be enough to support monophyly, we suggest the possibility that species with wing macrotrichiarestricted to the extreme tips of the membrane, like Polypedilum (Pentapedilum) tigrinum (Hashimoto, 1983), may be placed in the subgenus Polypedilum Kieffer, 1912.